دلالات العنف الرمزي كما يدركها التلاميذ وعلاقتها بإنجازهم الأكاديمي (دراسة ميدانية على عينة من تلاميذ المرحلة الثانوية) - وافي, رقية (Changement Social, 2019)
تهدف الدراسة الى التعرف على طبيعة العلاقة بين دلالات العنف الرمزي كما يدركه التلاميذ انجازهم الأكاديمي، حيث طبقت الدراسة على عينة مكوّنة من (100) تلميذ. ولتحقيق هذه الأهداف تبنت الباحثة مقياس العنف الرمزي لشاكو صفاء  ومقياس الإنجاز الأكاديمي لقشقوش والأعسر وأظهرت نتائج الدراسة أن أكثر دلالات العنف الرمزي ظهورا واتساما في المحيط المدرسي حسب إدراك التلاميذ له هي العلاقة بن المعلم والمتعلم والتقييم التعسفي، بالاضافة الي وجود علاقة ارتباطية دالة احصائية بين دلالات العنف الرمزي ومجالات الانجاز الأكاديمي، وايضا اظهرت النتائج وجود فروق دالة احصائيا بين التلاميذ المنجزين وغير المنجزين في إدراكهم لدلالات العنف الرمزي. الكلمات المفتاحية: دلالات العنف الرمزي، الانجاز الأكاديمي. The study aims to identify the nature of the relationship between the symbolic signs of violence as perceived by students academic achievement, where the study was applied to a sample of (100) students. In order to achieve these goals, the researcher adopted the measure of symbolic violence of Shaku Safa and the measure of academic achievement of Qashqoush and Al-Asr. The results of the study showed that the most symbolic signs of symbolic violence in the school environment are the relationship between teacher and learner and arbitrary evaluation. In addition, there is a statistical correlation between the signs of violence And the academic achievement. The results also showed statistically significant differences between students who completed and failed in their understanding of symbolic signs of violence. Keywords: symbolic violence, academic achievement